PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN, DAN UKURAN KAP TERHADAP AUDIT DELAY PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Khrisna Noor Seto; LMS Kristiyanti; Sri Laksmi Pardanawati (CV. Denasya Smart Publisher, 2025)
This research aims to determine the effect of profitability on audit delay in property and real estate company which is listed on the Indonesia Stock Exchange (IDX) period 2021-2023. The effect of solvability on audit delay in property and real estate company which is listed on the Indonesia Stock Exchange (IDX) period 2021-2023. The effect of the firm size on audit delay in property and real estate company which is listed on the Indonesia Stock Exchange (IDX) period 2021-2023. The effect of Public Accounting’s Size on audit delay in property and real estate company which is listed on the Indonesia Stock Exchange (IDX) period 2021-2023.This research was a causal comparative research with quantitative approach the samples were 35 companies by using purposive sampling. The data analysis technique used was descriptive statistics, precondition analysis test, hypothesis testing using multiple linear regression analysis. The results show that profitability has no effect on audit delay, Solvability has positive effect and significant on audit delay, The firm size has negative effect and significant on audit delay and The Public Accounting’s Size has no significant effect on audit delay.